PENERAPAN MODEL PEMBELAJARAN COOPERATIVE TEKNIK INSIDE OUTSIDE CIRCLE PADA MATA PELAJARAN IPS - Valensy Rachmedita; Maskun Maskun; Yustina Sri Ekwandari (PESAGI (Jurnal Pendidikan dan Penelitian Sejarah), 2014)
The aim of this research was to find out the positive effect of the implementation of cooperative learning model inside outside circle technique in increasing social students’ interest at the first grade of SMP Wiyata Karya Natar in academic year 2013/2014.  This research used experiment method. Based on data analysis, the result of this research shows that there is positive effect of the implementation of cooperative learning model inside outside circle technique in increasing social students’ interest. It can be seen from the percentage of measuring social students’ interest before learning positive category 37.04% and measuring after learning positive category 55.56%. Furthermore, there is an increase of the social students’ interest percentage of 18.52%.Tujuan dalam penelitian ini adalah untuk mengetahui pengaruh positif dari penerapan model pembelajaran cooperative teknik inside outside circle terhadap meningkatknya  minat belajar IPS siswa kelas VII SMP Wiyata Karya Natar tahun pelajaran 2013/2014.Penelitian ini menggunakan metode eksperimen.Berdasarkan analisis data diperoleh hasil penelitian yang menunjukan bahwa ada pengaruh  yang positif dari penerapan model pembelajaran cooperative teknik inside outside circle terhadap  meningkatnya minat belajar IPS siswa dilihat dari persentase pengukuran minat belajar siswa sebelum pembelajaran kategori positif 37,04% dan pengukuran sesudah pembelajaran kategori positif 55,56%, sehingga ada peningkatakan persentase minat belajar siswa 18,52 %.Kata kunci : inside outside circle, minat belajar, model pembelajaran